Supply Chain Management National Beverages Company (NBC) ( Coca Cola / Cappy ) - Yazan Toma; Alaa Yassin; Malik Ammar (My University, 2012)
National Beverages Company (Coca Cola/ Cappy) is one of the largest companies in the Palestinian market. The company applies an International system in quality control, management control with high standards of the non alcoholic beverages. But in the same time the company doesn't enjoy a precise system for inventory, warehouses, retailers and the information flow system. Our project is going to study and discuses these  matters. Supply Chain Management and other Industrial Engineering principles will be used in our project ending up with the final solutions  Represented by building the dynamic model of Inventory and warehouses in additional to building the information flow system in the company.   The study of Supply chain management in NBC  is essential in the company's success and customer satisfaction. The objectives in applying this project on NBC Company are: Reducing inventories along the chain, Better information sharing among the partners, Planning being done in consultation rather than in isolation. The benefits too would be reflected in terms of : Lower costs, Better customer service, Efficient manufacturing, Better trust among the partners. In this report we going to introduce an brief introduction of the components of the project, literature review, problem statement, methodology, what is the completion of the project so far, and the plane for the second semester.       Plan of the project and methodology:         Palestinian market study : Collection of the essential information in order to forecast the demand.       Logistic study of the Coca cola network in Palestine.       Checking the international standards of  Coca Cola.       Applying the supply chain strategies ( using mathematical applications) on our case-study ( Coca Cola ).       Ending up with the best for Coca Cola company in Palestine which can be implement in order to achieve all objectives.      Inventory and Warehouses system:   A-B-C classification  Analyzing of NBC products into three categories provides a mechanism for identifying the items that will have a significant impact on overall inventory cost. while also providing a mechanism for identifying different categories of stock that will require different management and controls.     Studying the demand and finding the best method for forecasting  Tracking the pattern of the demand in order to identify the best method for forecasting for example: Time series methods, methods for stationary series, trend-based methods, methods for seasonal series and Box-Jekins models.       Studying the inventory problems.     Determination of stock level.     Determination of safety stocks.      Selecting the proper system of ordering for inventory.     Determination of economic order quantity.     Building the dynamic inventory model.     Ending up with the final inventory model, which will be solution for our problem with numerical example.       Information flow system modifications and improvement:        Studying the information flow system of the company     Detecting and identifying the problems and the area for improvement      Build the information system for the company with the improvements and modifications    Ending up with final information flow system, which will be the solution for our problem.